The Ornamentation of Single Wooden Chairs in Jepara From The 17th to The 20th Century - Hariyanto, Eko; Mujiyono, Mujiyono (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
The ornamentation of single chairs is a crucial aspect in furniture design, contributing to the aesthetic value and beauty. This qualitative descriptive study utilized fieldwork data collection methods to delve into the chair ornamentation in Jepara, a coastal area in Central Java renowned for its carved furniture industry. This industry reaches all societal layers, from the low to the high income groups. The study identified a design revolution that shifted the focus of chair decoration from mere ornaments to form and function. Specifically, the ornamentation in the design of single wooden chairs in Jepara includes two main motifs: flora and fauna, as well as geometric. The study also explores how innovation in the ornamentation of Jepara's single chairs contributes to the competitiveness in local and international markets, highlighting the importance of design in the furniture industry. Furthermore, this research reveals the impact of the interaction between Jepara's carving art traditions and modern design trends, creating a unique synergy that enriches both cultural heritage and contemporary aesthetics. This analysis uncovers how each chair style with its respective ornamentation reflects the distinctive cultural and social background of the region.